27.7k views
1 vote
Solve the following iniquality:
2(2x – 3) ≥ –3(5x) + 5x

User Tuncalik
by
4.8k points

2 Answers

3 votes

Answer:

x ≥ 3/7

Explanation:

Step 1: Simplify both sides of the inequality.

4x−6 ≥ −10x

Step 2: Add 10x to both sides.

4x−6+10x ≥ −10x+10x

14x−6 ≥ 0

Step 3: Add 6 to both sides.

14x−6+6 ≥ 0+6

14x≥6

Step 4: Divide both sides by 14.

14x/14 ≥ 6/14

User AVH
by
5.4k points
2 votes

Answer:

x ≥ 3/7

Explanation:

2(2x - 3) ≥ -3(5x) + 5x

~Distribute both sides

4x - 6 ≥ -15x + 5x

~Simplify the right side

4x - 6 ≥ -10x

~Subtract 4x to both sides

-6 ≥ -14x

~Divide -14 to both sides

6/14 ≤ x

~Simplify

x ≥ 3/7

Best of Luck!

User Aonan Zhang
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.